2018
DOI: 10.1093/jas/skx073
|View full text |Cite
|
Sign up to set email alerts
|

Estimating optimal observational sampling frequency of behaviors for cattle fed high- and low-forage diets

Abstract: Video recordings of behavioral activities including eating, ruminating, drinking, standing, and lying were monitored to determine the minimum number of sampling days and sampling frequency required to obtain reliable estimates of these behaviors. Eight continental crossbred heifers, individually housed in a tie-stall barn with total mixed ration provided once per day, were divided by BW into two blocks and assigned to each of the two dietary treatments in a crossover design: high-forage diet (HF, forage:concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
(59 reference statements)
4
5
0
Order By: Relevance
“…The information about how 3-NOP in a diet influences feeding behavior of beef cattle is lacking. The durations of standing and lying of animals were similar to that of cattle in confined conditions (Dong et al, 2018). Meal frequency and duration were slightly greater for animals in the current study compared with other studies (Holtshausen et al, 2011;He et al, 2015;Dong et al, 2018), probably because DMI of animals in the current study was greater.…”
Section: Experiments 1: High-forage Dietsupporting
confidence: 46%
See 2 more Smart Citations
“…The information about how 3-NOP in a diet influences feeding behavior of beef cattle is lacking. The durations of standing and lying of animals were similar to that of cattle in confined conditions (Dong et al, 2018). Meal frequency and duration were slightly greater for animals in the current study compared with other studies (Holtshausen et al, 2011;He et al, 2015;Dong et al, 2018), probably because DMI of animals in the current study was greater.…”
Section: Experiments 1: High-forage Dietsupporting
confidence: 46%
“…The durations of standing and lying of animals were similar to that of cattle in confined conditions (Dong et al, 2018). Meal frequency and duration were slightly greater for animals in the current study compared with other studies (Holtshausen et al, 2011;He et al, 2015;Dong et al, 2018), probably because DMI of animals in the current study was greater. In addition, meal events (e.g., frequency and duration) can differ depending upon the measurement method of determining feeding behavior (e.g., GrowSafe system or video recording) and method of analyzing behavior data (fixed meal criterion or meal criterion analyzed using models; Bailey et al, 2012).…”
Section: Experiments 1: High-forage Dietsupporting
confidence: 46%
See 1 more Smart Citation
“…Thus, it might be possible to use the length of this latency period as an indication of risk of acidosis. In a study of nonlactating heifers fed diets of 70:30 or 30:70 F:C ratio (DM basis), a mean latency period of 19.4 min (range: 4.1-44.5) and 26.0 min (6.0-70.6), respectively, was observed (Dong et al, 2018). The mean rumen pH of cows in that study was 6.57 and 6.15, respectively.…”
Section: Assessment Of Ruminal Acidosis Riskmentioning
confidence: 79%
“…Video recordings are also time consuming because the scanning interval needs to be frequent such that accuracy of the estimates is not compromised (Hämäläinen et al, 2016). Dong et al (2018) recommended a minimum observational frequency of 2 d with 4-min intervals for eating time and 3 d with 4-min intervals for ruminating time. Bhandari et al (2008) reported a correlation coefficient of 0.94 between continuous monitoring and 5-min scan sampling of eating and ruminating behavior when observed over 3 d. Hämäläinen et al (2016) recommended a sampling interval of 4 min for eating activity and 15 min for ruminating.…”
Section: Measuring Chewing Timementioning
confidence: 99%